Need-adapted and Individualized Psychocardiological Intervention in Patients with Myocardial Infarction to Reduce Consequential Psychological Diseases - Maria Fadljevic; Claudia Christ; Joachim R. Ehrlich; Selina Raisch; Emilia Herlitzius (The Global Psychotherapist, 2023)
A heart attack is often a very drastic, sometimes even traumatic, life event for patients, which is frequently associated with fear of death. Not only is the body under enormous stress, a heart attack also means stress for the psyche. “Stressful life events are part of human existence and are compensated for with individual coping strategies or defense mechanisms. However, if the strain is overwhelming or the possible solutions are subjectively exhausted, pathological reactions may occur.”(1) From a psychosomatic perspective, an acute myocardial infarction is a “significant biographical breaking point with far-reaching psychological consequences.”(2) This pilot study investigates whether a psychocardiological intervention integrated into standard therapeutic care in the form of a structured conversation with a biopsychosocial model (in the sense of the WHO understanding of health), adapted to the patient’s level of need, can have a positive effect on quality of life and on psychological comorbidity in the short- and long-term course of recovery. 45 patients with acute myocardial infarction (13 female, 32 male), who were randomly assigned to two intervention groups, were followed for six months after the cardiac event with individualized and collaborative psychocardiological interventions and tested for mental illness. The results of the study show that such individualized care with additional screening for psychological comorbidities in the early phase after a myocardial infarction can significantly help patients to help themselves, provide early indications of the presence of a psychological disorder, and accelerate the initiation of adequate treatment. The integration of a psychocardiological component into the standard therapy of myocardial infarction patients in the early phase after the cardiac event seems to be a valuable contribution to the therapy and should receive encouragement in the future. Furthermore, this pilot study offers new and interesting approaches for future research.